Building a Dialog Room: Protecting Minorities in Indonesia - Syahrul Kirom (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
At the end of 2020, cases of religious violence in Indonesia reappeared. Such as the case of the destruction of musala Al-Hidayah building in Perum Agape, Tumaluntung Village, Kauditan Subdistrict, North Minahasa Regency, North Sulawesi Province. This study uses a descriptive-analytical approach. To analyze every socio-religious case that occurred in Indonesia. Meanwhile, the Hermeneutic method interprets socio-religious issues with the theoretical framework of Jurgen Habermas' thought. The results of this study need to build dialogue between religious communities in Indonesia without any intervention from one particular religion so that the dialogue space can run well and peacefully. By emphasizing communicative rationality in understanding religious differences or beliefs in establishing harmonious relations between religious communities in Indonesia and prioritizing the three principles of religious harmony supported by implementing the values of Pancasila and Bhinneka Tunggal Ika as unity and oneness in knitting religious tolerance.